Optimization of process parameters for the selective leaching of copper, nickel and isolation of gold from obsolete mobile phone PCBs - Rao M.D.; Singh K.K.; Morrison C.A.; Love J.B. (My University, 2025)
The sequential separation of base and precious metals from the end-of-life mobile phone printed circuit boards (PCBs) is a significant challenge for the development of recycling process that exhibit material circularity. In this contribution, a simple, eco-friendly, and efficient leaching process is developed for the dissolution of copper and nickel from obsolete mobile phone PCBs to facilitate the isolation of a gold-rich residue. Chemical pre-treatment of downsized PCBs produced a metallic portion for which the leaching parameters for copper and nickel were optimised, including the type of leaching reagent, temperature, time, pulp density and agitation speed. It was found that quantitative dissolution of base metals occurred using 3.0 M nitric acid at 30 °C with a 50 g/L pulp density, 2 h residence time, and 500 rpm stirring speed; under these conditions, no gold was dissolved. Design of Experiment analysis using Response Surface Methodology was also undertaken to validate the process. Finally, the kinetics of the leaching process were studied and shown to conform to the chemically controlled surface reaction model, with activation energies of 39.7 and 18.4 kJ/mol for copper and nickel. Importantly, the leaching process optimised in this work avoids the need for high temperatures and reduces energy consumption and effluent generation, leading to the cleaner processing of obsolete mobile phone PCBs for the separation of gold from the dominant base metals. © 2021 The Authors